2015
DOI: 10.3402/fnr.v59.25765
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with complex milk lipids during brain development promotes neuroplasticity without altering myelination or vascular density

Abstract: BackgroundSupplementation with complex milk lipids (CML) during postnatal brain development has been shown to improve spatial reference learning in rats.ObjectiveThe current study examined histo-biological changes in the brain following CML supplementation and their relationship to the observed improvements in memory.DesignThe study used the brain tissues from the rats (male Wistar, 80 days of age) after supplementing with either CML or vehicle during postnatal day 10–80. Immunohistochemical staining of synapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 34 publications
(56 reference statements)
0
17
0
Order By: Relevance
“…60 Systemic Effects of SL Details in this area are outside the scope of this article. An interesting example is that polar lipids in milk were shown to increase neuronal plasticity in the brain of rats 61 and improve spatial memory learning, which could be linked to astrocyte and synaptic functions in a region of the hippocampus. Cognitive behavior improved in a small pilot study of SM-fortified milk in low birth-weight infants.…”
Section: Sm Npp7 and Cholinementioning
confidence: 99%
“…60 Systemic Effects of SL Details in this area are outside the scope of this article. An interesting example is that polar lipids in milk were shown to increase neuronal plasticity in the brain of rats 61 and improve spatial memory learning, which could be linked to astrocyte and synaptic functions in a region of the hippocampus. Cognitive behavior improved in a small pilot study of SM-fortified milk in low birth-weight infants.…”
Section: Sm Npp7 and Cholinementioning
confidence: 99%
“…In a recent study designed to probe the possible mechanisms through which ganglioside/CML supplementation might improve spatial learning and memory in postnatal rats, as observed in an earlier trial [ 137 ], our group found that CML supplementation (1% w/w of diet) may enhance neuroplasticity in the CA3 hippocampal region of young normal rats during development, possibly through enhanced synaptogenesis [ 151 ]. Our data also indicated that improved cognitive function of CML supplementation did not associate with either vascular remodeling or glutamatergic neuroplasticity in the hippocampus, striatum, and frontal cortex of young normal rats but may be associated with changes in the nigral-striatal dopaminergic pathway, which also plays a key role in learning and memory.…”
Section: Mechanistic Studies Of Dietary Ganglioside Effect On Cognmentioning
confidence: 99%
“…Gelatin cubes were used for administration of the dietary supplements, which were formulated using raspberry flavouring and gelatin (10% w/v) containing sucrose (10% w/v) as previously described [32, 33, 36, 44]. Briefly, the MFGM mixtures were dissolved in water using a food processor and were then mixed with 1 L of gelatin/sucrose mixture at 50 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Three different MFGM mixtures were tested; they were administered at various absolute doses so as to match the administered amount of gangliosides (GD3), an established brain bioactive molecule [35]. The bovine-derived MFGM supplements tested included a complex milk lipid (CML) mixture (reported previously in [33, 35, 44]), beta serum concentrate (BSC) (reported previously in 32) and a polar-lipid-enriched complex milk lipid concentrate (CMLc, “PGC80”) that lacks an MFGM protein component (reported previously in 36). The dose of CML used and the standardised ganglioside concentration were based on our previously published study in which developing rats received dietary supplementation with CML containing 5.9% gangliosides, at a dose of 1% w/w of dietary intake [35].…”
Section: Methodsmentioning
confidence: 99%